The Relative Immunogenicity of HLA Mismatches in Adult Liver Transplant Patients from the ITN A-WISH Trial. (July 2018) - Jucaud, Vadim; Shaked, Abraham; DesMarais, Michele; Sayre, Peter; Everly, Matthew J
Abstract : N/A: Determining the immunogenicity of HLA mismatches (MM) may help preventing the appearance of de novo DSA (dnDSA) and avoiding antibody-mediated injuries. We studied the development of dnDSA against the HLA-A, -B, -C, -DR and -DQ MM (high resolution) in a cohort of 69 liver transplant patients from the A-WISH trial, which was designed to determine the clinical benefit of early immunosuppression (IS) withdrawal. A total of 764 MM were studied. DQB1 MM were significantly more immunogenic than MM from other loci (p<0.0001). No dnDSA were clearly against DQA1. Forty percent of dnDSA onset was during IS maintenance, and 60% during IS minimization/withdrawal. Among HLA-DQ MM, DQB1*03:01 was the most immunogenic where 63% MM led to the formation of dnDSA, followed by DQB1*02:01 (54%), DQB1*03:02 (50%), DQB1*06:09 (50%), DQB1*04:02 (43%), DQB1*05:03 (33%), DQB1*05:01 (26%), DQB1*06:04 (20%), DQB1*06:03 (17%), and DQB1*02:02 (8%). Among HLA-DR MM, the immunogenicity was highest for DRB1*04:03 (50%), followed by DRB1*08:01 (33%), DRB5*01:01 (20%), DRB4*01:03 (17%), DRB1*03:01 (15%), DRB3*03:01 (10%), and DRB1*07:01 (8%). Last, among HLA-I MM, the immunogenicity was highest for C*17:01 (33%), followed by B*44:02 (20%), A*29:02 (17%), A*24:02 (8%), and B*35:01 (7%). A great number of MM did not lead to the formation of dnDSA, listed in the table, despite their high frequency. HLA-DQ MM are the most immunogenic compared to MM from other HLA loci. Highly immunogenic MM should be considered to prevent the development of dnDSA and antibody mediated graft injury. Many MM did not induce dnDSA and are not likely to be immunogenic, hence these MM may be considered permissible.